2018
DOI: 10.1136/bmjdrc-2018-000519
|View full text |Cite
|
Sign up to set email alerts
|

GOAL study: clinical and non-clinical predictive factors for achieving glycemic control in people with type 2 diabetes in real clinical practice

Abstract: ObjectiveThe American Diabetes Association and the European Association for the Study of Diabetes guidelines recommend to individualize treatment targets/strategies in inadequately controlled patients by lifestyle management and glucose-lowering drugs to decrease the burden of diabetes-related complications. This real-world practice study aimed to assess predictive factors for achieving the glycemic hemoglobin A1c (HbA1c) at 6 months as targeted by the treating physician in adults with type 2 diabetes who requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 35 publications
5
38
0
3
Order By: Relevance
“…We observed that younger people had worse glycaemic control than people aged >60 years. This finding has also been reported in other countries . A large observational study in Sweden showed that people with type 2 diabetes aged <55 years had the highest increase in risk of cardiovascular disease and death compared with similarly aged controls .…”
Section: Discussionsupporting
confidence: 83%
“…We observed that younger people had worse glycaemic control than people aged >60 years. This finding has also been reported in other countries . A large observational study in Sweden showed that people with type 2 diabetes aged <55 years had the highest increase in risk of cardiovascular disease and death compared with similarly aged controls .…”
Section: Discussionsupporting
confidence: 83%
“…26 La utilización de medicamentos no se asoció con un mejor control glucémico, lo que se puede explicar por el escalamiento proporcional del tratamiento al nivel de avance de la enfermedad. 27 Sin embargo, también debe considerarse que en México se ha reportado una carencia al apego a la guía de práctica clínica y las recomendaciones de la ADA, lo que dificulta el seguimiento del paciente y su adherencia al tratamiento. 26 Hasta el momento, no se ha logrado asegurar un control glucémico adecuado en pacientes que viven con diabetes.…”
Section: Discussionunclassified
“…С учетом изложенного при прочих равных условиях преимущество имеют препараты, действие которых не связано со стимуляцией бета-клеток. Осложнения СД 2-го типа связаны не только с гипергликемией, но и с дислипидемией, артериальной гипертензией, гиподинамией, курением и другими факторами, что требует индивидуального подхода [114].…”
Section: выводыunclassified